Agreement Between Bioelectrical Impedance and Dual-Energy X-Ray Absorptiometry to Track Changes in Fat-Free Mass After Resistance Training in Older Women - Nascimento, Matheus A. [UNESP]; Silva, Danilo R. P.; Ribeiro, Alex S.; Pina, Fabio L. C.; Gerage, Aline M.; Gobbo, Luis A. [UNESP]; Mayhew, Jerry L.; Cyrino, Edilson S. (Lippincott Williams & Wilkins, 2020)
Nascimento, MA, Silva, DRP, Ribeiro, AS, Pina, FLC, Gerage, AM, Gobbo, LA, Mayhew, JL, and Cyrino, ES. Agreement between bioelectrical impedance and dual-energy x-ray absorptiometry to track changes in fat-free mass after resistance training in older women. J Strength Cond Res 34(6): 1700-1708, 2020-The aim of our study was to compare the agreement between bioelectrical impedance (BIA) and dual-energy X-ray absorptiometry (DXA) to track changes on fat-free mass (FFM) after a resistance training (RT) program in older women. Forty-three older women (65.2 +/- 4.6 years, 59.5 +/- 9.2 kg, 156.4 +/- 6.0 cm, 24.3 +/- 3.3 kg center dot m(-2)) participated in a RT intervention (12 weeks, 8 exercises, 2 sets, 10-15 repetitions, 3 nonconsecutive days per week). Fat-free mass changes were determined by a single-frequency BIA device (EQ1), 6 BIA prediction equations for older women (EQ2, EQ3, EQ4, EQ5, EQ6, and EQ7), and DXA. At pretraining, 3 equations overpredicted, and 3 underpredicted DXA FFM (F = 244.63, p < 0.001), although all equations had high correlations with DXA (r = 0.78-0.83). After training, 4 equations overpredicted and one underpredicted DXA FFM (F = 176.25, p < 0.001). Dual-energy X-ray absorptiometry detected significant gains in FFM (0.65 +/- 0.82 kg; p < 0.05), as did EQ3 (0.55 +/- 1.69 kg; p < 0.05), and EQ4 (0.61 +/- 1.88 kg; p < 0.05), whereas the remaining equations did not indicate significant changes in FFM. Low correlations between FFM and equation change values suggest that single-frequency BIA-derived equations may not provide sufficient accuracy to track changes in FFM after 12 weeks of RT in older women.
Keywords: DXA; BIA; strength training; BMI